Synthesis and Characterization of a New Cyclophosphazene and Its Ruthenium Complex Derived from 1,10-Phenanthroline-5,6-diol - Karaoglan, Gulnur Keser; Erden, Ibrahim; Demirhan, Nebahat (ASIAN JOURNAL OF CHEMISTRY, 2013)
A new spirocyclic phosphazene derivative has been synthesized from the reaction of 1,10-phenanthroline-5,6-diol with hexachlorocyclotriphosphazatriene in suitable conditions and the Ru(II) complex of the ligand was prepared and characterized. Synthesized compounds have been investigated with the methods of FTIR, H-1 NMR, P-31 NMR, UV-VIS, MS, fluorescence and elemental analysis.
Keywords: Spirocyclic phosphazene; Ruthenium complex; 1,10-Phenanthroline; POLY(ORGANOPHOSPHAZENES); DERIVATIVES; BEHAVIOR; SPIRO; Chemistry